Genotyping analysis of MNS blood group GP(B‐A‐B) hybrid glycophorins in the Chinese Southern Han population using a high‐resolution melting assay. Issue 7 (13th June 2018) - Wei, Ling; Lopez, Genghis H.; Zhang, Yang; Wen, Jizhi; Wang, Zhen; Fu, Yongshui; Hyland, Catherine A.; Flower, Robert L.; Luo, Guangping; Ji, Yanli
Abstract : BACKGROUND: MNS hybrid GP(B‐A‐B) glycophorins are more commonly found in Southeast Asians and alloantibodies to antigens they carry are clinically significant. Detection of hybrid glycophorins by serologic techniques is limited due to lack of commercial reagents. In this study, a genotyping method for GP(B‐A‐B) hybrid glycophorins based on high‐resolution melting (HRM) analysis was applied for genotyping analysis in the Chinese Southern Han population. STUDY DESIGN AND METHODS: DNA samples from 3104 Chinese Southern Han blood donors were collected. GYP(B‐A‐B) genotypes were analyzed by HRM assay. Parts of samples (n = 106) were also tested by multiplex ligation‐dependent probe amplification (MLPA) assay. Direct sequencing was conducted in samples with variant melting curve profiles. RESULTS: A total of five GYP(B‐A‐B) genotypes (201/3104, 6.5%) were identified, which were GYP*Mur heterozygote ( n = 194), GYP*Mur homozygote ( n = 3), GYP*Bun heterozygote ( n = 2), GYP*HF heterozygote ( n = 1), and a novel GYP(B‐A‐B) hybrid allele ( n = 1). Genotyping results for GYP*Mur and wild‐type GYPB samples obtained by HRM were consistent with MLPA, while GYP*Bun and GYP*HF heterozygote identified by HRM could only be identified to have one copy of 5′ inactive splice site of GYPB Pseudoexon 3 by MLPA. In addition, 10 single‐nucleotide polymorphisms (SNPs) including four known and six novel SNPs were identified in 31 samples. One sample was identified carrying both GYP*Mur and GYP*Sch alleles. CONCLUSION: The HRM assay could distinguish the GYP(B‐A‐B) hybrid alleles successfully. Polymorphisms identified within the GYPB gene should be taken into consideration when developing GYP(B‐A‐B) genotyping kits for the Chinese population.